Crowdfunding: analisis SWOT dan digital marketing - Lena Lestary; Heny Hendrayati; Agus Rahayu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The impact of the pandemic on MSMEs is believed to be greater than other sectors. One solution for MSMEs at this time is the Financial Technology strategy as the basis for a fiscal strategy because of its ability to increase financial transactions in the economy. Crowdfunding, which is one part of fintech, is currently emerging as an alternative for the government through the OJK in overcoming MSME funding problems. The research method used is descriptive. In Indonesia, crowdfunding is not familiar to investors or the public. This can be seen from the data that crowdfunding users are in the range of only 6% of all fintech users. Companies of Crowdfunding fintech have been doing digital marketing with various means such as websites and social media Instagram. However, where crowdfunding users are still very few compared to other types of fintech. For this reason, the authors suggest that companies can improve the quality of information that appears on websites, mobile applications, or social media both in terms of content and graphic design to make it look more attractive and informative, then sharpen the SWOT analysis so that better strategies can be found. to promote crowdfunding companies as well as MSMEs.